Social-Scientific Collaboration and Local Wisdom with Bilingual Learning for 21st-Century Competencies - Kusuma Wardana, Bagaskara Fajareto (Journal of Language, Literature and Teaching, 2025)
This study examines the integration of social-scientific collaboration and local wisdom through bilingual learning to develop 21st-century competencies. This qualitative, descriptive phenomenological research was conducted with eighth-grade students at Muhammadiyah 1 Junior High School Kartasura. Data was collected via in-depth interviews, participant observation, and document analysis, validated through source and technique triangulation, as well as member checking. The results indicate that interdisciplinary integration Social Studies, Natural Sciences, Javanese Language, and English, combined with local wisdom and bilingual learning, significantly enhances students critical thinking, creativity, collaboration, character, and cultural identity. Project-based learning relevant to daily life and local culture fosters greater student engagement, confidence, and active participation. Phenomenological analysis reveals that students experience more meaningful and contextual learning, gaining a deeper understanding of social and cultural values, alongside increased pride and emotional attachment to their local culture. Students are able to connect academic concepts with real-life experiences, enhancing motivation and learning quality.